Experimental study of dynamic damage of an arch dam. - Wang, Haibo
Seismic responses of a 292-m high arch dam were studied by experiment on a shaking table. The model system included the arch dam with contraction joints, a part of a reservoir, and a partial foundation with a topographic feature near the dam. Potential rock wedges on the abutments and the mechanical properties including uplift on the kinematic planes were carefully simulated. A damping boundary consisting of a viscous liquid was introduced to simulate the effect of dynamic energy emission to far field, which made the dynamic interaction between the dam and the foundation be adequately represented in the model test of an arch dam system. Dynamic responses of the arch dam system under a sequence of seismic loadings in increasing strength were examined. Eleven cracks or overstresses on the model dam due to the earthquake excitations were observed, and consequently, its natural frequency dropped by about 14%, but the model dam was stable under the hydrostatic load of the impounded water after the test.
Keywords: Arch dam; Damage; Seismic resistance; Damping boundary; Shaking table; Abutment wedge